Galactolipid and Phospholipid Profile and Proteome Alterations in Soybean Leaves at the Onset of Salt Stress - Liu, Ailin; Xiao, Zhixia; Wang, Zhili; Lam, Hon-Ming; Chye, Mee-Len (Frontiers in Plant Science, 2021)
Salinity is a major environmental factor that constrains soybean yield and grain quality. Given our past observations using the salt-sensitive soybean (Glycine max [L.] Merr.) accession C08 on its early responses to salinity and salt-induced transcriptomic modifications, the aim of this study was to assess the lipid profile changes in this cultivar before and after short-term salt stress, and to explore the adaptive mechanisms underpinning lipid homeostasis. To this end, lipid profiling and proteomic analyses were performed on the leaves of soybean seedlings subjected to salt treatment for 0, 0.5, 1, and 2 h. Our results revealed that short-term salt stress caused dynamic lipid alterations resulting in recycling for both galactolipids and phospholipids. A comprehensive understanding of membrane lipid adaption following salt treatment was achieved by combining time-dependent lipidomic and proteomic data. Proteins involved in phosphoinositide synthesis and turnover were upregulated at the onset of salt treatment. Salinity-induced lipid recycling was shown to enhance jasmonic acid and phosphatidylinositol biosyntheses. Our study demonstrated that salt stress resulted in a remodeling of membrane lipid composition and an alteration in membrane lipids associated with lipid signaling and metabolism in C08 leaves.